SIMCOP: Um Framework para Análise de Similaridade em Sequências de Contextos - Wiedemann, Tiago (Universidade do Vale do Rio dos Sinos, 2014)
The Ubiquitous Computing, that studies the ways to integrate technology into the people’s everyday life, is an area that has been growing in recent years, especially due to the development of technologies such as mobile computing. A key for the development of this type of application is the issue of context awareness, which enables an application to self adapt to the situation in which the user is currently on. To make this possible, it was necessary to formally define what is a context and how to represent it . From this formalization, techniques for analyzing contextual data have been proposed for development of functions as predictions or inferences. This paper specifies a framework called SIMCOP (SIMilar Context Path ) for performing the analysis of similarity between sequences of contexts visited by an entity. This type of analysis enables the identification of similar contexts with the intention to provide features such as the recommendation of entities and contexts, the entities classification and the prediction of contexts. The development of this research shows that the contexts similarity analysis can be useful in other areas further the ubiquitous computing, such as data mining and collaborative filtering systems. Any data type that can be described as a context, can be analyzed through the techniques of similarity analysis implemented by the framework, as demonstrated in the assessments.
Keywords: Data mining; Semantic similarity; Sequences similarity; Context sequences; Similarity analysis; Mineração de dados; Similaridade semântica; Similaridade entre sequências; Sequências de contextos; Análise de similaridade; ACCNPQ::Ciências Exatas e da Terra::Ciência da Computação